An analysis of the Brazilian higher educational opportunity and challenge processes to achieve the 2030 Agenda for the sustainable development (2023)
Purpose Population worldwide has experienced several challenges related to sustainable development, such as scarcity of natural resource, unsustainable consumption, poverty, injustice, violence, social inequality and natural disaster (including floods, ts